The Intoxication Effects of Methanol and Formic Acid on Rat Retina Function - Dong-Mei Liu; Shu Zhou; Jie-Min Chen; Shu-Ya Peng; Wen-Tao Xia (Journal of Ophthalmology)
Objective. To explore the potential effects of methanol and its metabolite, formic acid, on rat retina function. Methods. Sprague-Dawley rats were divided into 3- and 7-day groups and a control. Experimental groups were given methanol and the control group were provided saline by gavage. Retinal function of each group was assessed by electroretinogram. Concentrations of methanol and formic acid were detected by GC/HS and HPLC, respectively. Results. The a and b amplitudes of methanol treated groups decreased and latent periods delayed in scotopic and photopic ERG recordings. The summed amplitudes of oscillatory potentials (OPs) of groups B and C decreased and the elapsed time delayed. The amplitudes of OS1, OS3, OS4, and OS5 of group B and OS3, OS4, and OS5 of group C decreased compared with the control group. The IPI1 of group B and IPI1-4 of group C were broader compared with the control group and the IPI1-4 and ET of group B were broader than group C. Conclusions. Both of scotopic and photopic retinal functions were impaired by methanol poisoning, and impairment was more serious in the 7-day than in the 3-day group. OPs, especially later OPs and IPI2, were more sensitive to methanol intoxication than other eletroretinogram subcomponents.